Biomarkers in acute kidney injury – pathophysiological basis and clinical performance. (25th August 2016) - Schrezenmeier, E. V.; Barasch, J.; Budde, K.; Westhoff, T.; Schmidt‐Ott, K. M.
Abstract: Various biomarkers of acute kidney injury (AKI) have been discovered and characterized in the recent past. These molecules can be detected in urine or blood and signify structural damage to the kidney. Clinically, they are proposed as adjunct diagnostics to serum creatinine and urinary output to improve the early detection, differential diagnosis and prognostic assessment of AKI. The most obvious requirements for a biomarker include its reflection of the underlying pathophysiology of the disease. Hence, a biomarker of AKI should derive from the injured kidney and reflect a molecular process intimately connected with tissue injury. Here, we provide an overview of the basic pathophysiology, the cellular sources and the clinical performance of the most important currently proposed biomarkers of AKI: neutrophil gelatinase‐associated lipocalin (NGAL), kidney injury molecule‐1 (KIM‐1), liver‐type fatty acid‐binding protein (L‐FABP), interleukin‐18 (IL‐18), insulin‐like growth factor‐binding protein 7 (IGFBP7), tissue inhibitor of metalloproteinase 2 (TIMP‐2) and calprotectin (S100A8/9). We also acknowledge each biomarker's advantages and disadvantages as well as important knowledge gaps and perspectives for future studies.